Endoscopic small-capacity forceps increase the pathological diagnosis of gastric indefinite neoplasia - Matsuo, Yasumasa; Yasuda, Hiroshi; Kato, Masaki; Kiyokawa, Hirofumi; Ozawa, Midori; Sato, Yoshinori; Ikeda, Yoshiko; Ozawa, Shun-ichiro; Yamashita, Masaki; Fujino, Takashi; et al. (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: A definitive biopsy-based diagnosis of gastric cancer is sometimes difficult, and some cases are pathologically diagnosed as gastric indefinite neoplasia (GIN). The most appropriate forceps size for gastric biopsy has yet to be determined. In this study, we investigated the relation between the forceps size and the frequency of GIN diagnosis. Materials and Methods: The records of patients from two historical groups were reviewed. The first group comprised patients evaluated during the period when standard biopsy forceps (StF) were used (April 2010-March 2011), and the second group comprised patients evaluated during the period when small biopsy forceps (SmF) were used (April 2011-March 2013). Patients in whom GIN lesions were diagnosed with biopsy were identified, and pertinent data were compared between the two groups of patients. Results: Among the 8,420 patients who underwent esophagogastroduodenoscopy (EGD) during the first period, 2,584 (30.7%) underwent gastric biopsy with StF. Among the 15,968 patients who underwent EGD during the second period, 4,204 (26.3%) underwent gastric biopsy with SmF. GIN was diagnosed in a significantly greater number of patients in the SmF group than in the StF group (52 [1.25%] vs. 19 [0.73%]; p=0.048). The mean minor-axis lengths of the biopsy samples were 1.50±0.50 mm and 1.38±0.40 mm in the StF group and the SmF group, respectively, with the SmF group samples tending to be shorter (p=0.088). Conclusion: Because the SmF use may increase the rate of GIN diagnosis, the use of SmF with a standard-caliber endoscope should be avoided. Cite this article as: Matsuo Y, Yasuda H, Kato M, et al. Endoscopic small-capacity forceps increase the pathological diagnosis of gastric indefinite neoplasia. Turk J Gastroenterol 2018; 29: 481-7.